2022
DOI: 10.3390/diagnostics12102379
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Biomarkers and Chest CT Findings as Predictors of Acute Limb Ischemia Risk, Intensive Care Unit Admission, and Mortality in COVID-19 Patients

Abstract: Background: Numerous tools, including inflammatory biomarkers and lung injury severity scores, have been evaluated as predictors of thromboembolic events and the requirement for intensive therapy in COVID-19 patients. This study aims to verify the predictive role of inflammatory biomarkers [monocyte to lymphocyte ratio (MLR), neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), systemic inflammatory index (SII), Systemic Inflammation Response Index (SIRI), and Aggregate Index of Systemic I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 63 publications
(82 reference statements)
2
38
0
Order By: Relevance
“…This work supplements the previous two studies published by our group of researchers, Arbanasi et al and Halmaciu et al, which revealed the role of inflammatory markers in the prediction of ICU admission, IMV necessity, ALI risk, and mortality [ 45 , 46 ]. The hypercoagulability status of COVID-19 patients is well known, and the unpredictable evolution of these fragile patients, as well as the presence of comorbidities and risk factors, requires the establishment of prognostic tools and stratification of patients for better management of their health.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This work supplements the previous two studies published by our group of researchers, Arbanasi et al and Halmaciu et al, which revealed the role of inflammatory markers in the prediction of ICU admission, IMV necessity, ALI risk, and mortality [ 45 , 46 ]. The hypercoagulability status of COVID-19 patients is well known, and the unpredictable evolution of these fragile patients, as well as the presence of comorbidities and risk factors, requires the establishment of prognostic tools and stratification of patients for better management of their health.…”
Section: Discussionsupporting
confidence: 88%
“…Numerous research studies have been published in the last two years on the predictive significance of inflammatory markers and the mortality of COVID-19 patients [ 45 , 46 , 48 , 49 , 50 , 51 , 58 , 59 , 60 , 61 , 62 ]. Among the analyzed markers, NLR has the greatest interest for researchers, whose optimal cut-off value varies between 6.883 and 11.57 [ 48 , 50 , 51 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the systemic inflammatory biomarkers, the most accessible and easy to implement in current medical practice are hematological reports based on the total number of monocytes, neutrophils, lymphocytes, and platelets, respectively: monocyte-to-lymphocyte ratio (MLR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic inflammatory index (SII), systemic Inflammation Response Index (SIRI), and aggregate index of systemic inflammation (AISI), whose predictive role has been demonstrated in the case of cardiovascular pathologies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], oncological pathologies [ 24 , 25 , 26 , 27 ], chronic kidney disease [ 28 , 29 , 30 ], and, more recently, in the case of COVID-19 patients [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%